Validity and reproducibility of a food frequency questionnaire assessing food group intake in the PERSIAN Cohort Study - Eghtesad, Sareh; Hekmatdoost, Azita; Faramarzi, Elnaz; Homayounfar, Reza; Sharafkhah, Maryam; Hakimi, Hamid; Dehghani, Ali; Moosazadeh, Mahmood; Mortazavi, Zinat; Pasdar, Yahya; Poustchi, Hossein; Willett, Walter C.; et al. (Frontiers in Nutrition, 2023)
PURPOSE: A semi-quantitative food frequency questionnaire (FFQ) was developed for use in the Prospective Epidemiological Research Studies in IrAN (PERSIAN Cohort), investigating non-communicable disease risk factors.This study aimed to assess the validity and reproducibility of this FFQ, through food group intake. METHODS: Participants, recruited from seven PERSIAN cohort centers, completed the FFQ at the beginning of the study (FFQ1) and at the end (FFQ2), with a 12-month interval in between, during which two 24-hour dietary recalls (24HRs) were completed each month. Correlation coefficients of the median intake of food groups recorded by the FFQs were compared to those of the 24HRs to assess validity, and the two FFQs were compared to assess reproducibility of findings. RESULTS: Overall, data from 978 participants were included in this validation analysis. Of the 26 food groups assessed, Tea, Sugars, Whole/Refined Grains, and Solid Fats/Oils, had the strongest correlations (0.6-0.79), while Red Meat, Chicken and Eggs showed moderate correlations (0.42-0.59). The weakest correlations observed belonged to Fresh fruit Juice and Other Meats (0.23-0.32). Reproducibility was assessed among those who completed both FFQ1 and FFQ2 (n=848), revealing moderate to strong correlations in all food groups, ranging from 0.42 in Legumes to 0.72 in both Sugar and Sweetened Drinks.The PERSIAN Cohort FFQ is appropriate to rank individuals based on food group intake.